Thin, flexible supercapacitors made from carbon nanofiber electrodes decorated at room temperature with manganese oxide nanosheets - Nataraj, S. K.; Song, Q.; Al-Muhtaseb, S. A.; Dutton, S.; Zhang, Qi; Sivaniah, E. (Hindawi Publishing Corporation, 2013)
We report the fabrication and electrochemical performance of a flexible thin film supercapacitor with a novel nanostructured composite electrode. The electrode was prepared by in situ coprecipitation of two-dimensional (2D) MnO2 nanosheets at room temperature in the presence of carbon nanofibers (CNFs). The highest specific capacitance of 142 F/g was achieved for CNFs-MnO2 electrodes in sandwiched assembly with PVA-H4SiW12O40.nH2O polyelectrolyte separator.